The Implementation of Computer Assisted Language Learning (CALL) to Improve Speaking Ability of Students in Bali State Polytechnic - Ni Nyoman Yuliantini; I Nyoman Rajin Aryana; I Gusti Putu Sutarma; Gusti Ayu Oka Cahya Dewi (OKARA: Jurnal Bahasa dan Sastra, 2020)
Preliminary observations conducted in Bali State Polytechnic found that the students' learning outcomes in speaking were still shallow. Modern facilities equipped with advanced technology such as computer devices known as CALL (Computer Assisted Language Learning) are vital to helping lecture in language teaching and learning process, including speaking. This study aims to improve student speaking learning outcomes in English courses by conducting CALL and how CALL can make a contribution in increasing speaking ability in Vocational Higher Education.  The research method used in this research was mix method approach. The subjects were the students of Electrical Engineering, Bali State Polytechnic. The data were analyzed quantitatively and descriptively. The results showed that the video-assisted CALL method's application could improve student learning outcomes in English courses.int shows the differences in the pre-test and post-test results, where there is an increase of 14.34%. Besides, the CALL method also allows students to have more expressive activities in presenting conversation among their friends to feel happy and interested. Similarly, CALL can also create fun learning since the students learn using the internet and computer, which are commonly used